Laju Pertumbuhan Rotifera (Branchionus plicatilis) di Media Kultur Berdasarkan Jenis Pakan Kombinasi - Reza Yunita Sari; Ni Luh Watiniasih; Suprabadevi Ayumayasari Saraswati (Current Trends in Aquatic Science, 2019)
Availability of rotifera natural food needs to be increased in line with the increasing need for larvae feed in fish hatchery production activities. This study aims to analyze the effect of different feeds on the growth rate of rotifers (Branchionus plicatilis). This research was conducted in December 2018 to January 2019 at the Jepara Brackishwater Aquaculture Center. This study used a completely randomized design with 4 treatments and 3 repetitions, namely control (N. ocullata), treatment 1 (N. ocullata + bread yeast), treatment 2 (N. ocullata + scott emultion), treatment 3 (N. ocullata+ fish powder). The dosages of each feed were 170,000 cells / ind N. ocullata, 0.5 g / 106 rotifera bread yeast per day, 6 µg / ind scott emultion, and 0.3 g /106/ind fish powder. Feeding is done twice a day in the morning and evening. The test plankton used was 15 ind / ml Branchionus plicatilis. Rotifera culture was carried out for 6 days and the population of rotifers was observed every day before feeding. Analysis of water quality was also carried out including DO, salinity, pH, temperature, and ammonia. The rotifera growth rate is analyzed through the number of individuals produced during the culture period. The results showed that treatment 3 (N. ocullata + fish powder) was the best treatment. The results of the ANOVA test showed that different feeding variations for each treatment had a significant effect (P <0.05) on the rotifera growth rate.